A experiência de gestão do Projeto Rio 2016 - Gonçalves, Juliana da Silva (2013)
The goal of this research is analyse the experience of management and development of the Rio 2016 Social Project, directing comments to the comparison between the design and planning of Public Policy and its actual implementation. Were observed documents conceptually organize the project, which favored the understanding of how their managers perceive and orient such Public policy. From the extraction of arguments reasoning of such policy documents, analyzed the distortions between the theoretical discourse presented and its implementation in the practical field. The management and operational strategies presented, coupled with observing the everyday development of the Project have identified the main difficulties encountered by the implementation of the policy coordination team and failures from the process as a whole, which provided the basis for production of suggestions for adequacy and empowerment policy under review.